The Application of Islamic Religious Education to Child Behavior (Case Study of Factory Worker Family in The Ngoro Industrial Park (NIP) Area, Ngoro District, Mojokerto Regency) - Najah, Faizun; Mashuda, Agus (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to examine the application of Islamic religious education to children's behavior (Case Study of Factory Workers' Families in the Ngoro Industrial Park (Nip) Area, Ngoro District, Mojokerto Regency) using a qualitative research methodology. Based on the study's results, first, the application of Islamic religious education is by giving examples, habituation, advice, attention, gifts, and punishments with basic Islamic religious materials about faith, prayer, morality, and reading the Qur'an and Islamic history. Second, with this application, even though a child is sometimes not supervised by his parents due to busy work, he still behaves Islamically as his parents have applied.